The 2025 CHINET surveillance report on bacterial resistance in China - Li Ding; Yan Guo; Siquan Shen; Renru Han; Dandan Yin; Jinye Du; Xiuwen Xu; Yang Yang; Shi Wu; Demei Zhu; Fupin Hu (One Health Advances, 2026)
Abstract This study assessed the antimicrobial susceptibility of clinical bacterial isolates collected from Chinese medical institutions in 2025. Antimicrobial susceptibility testing was performed on isolates from 80 hospitals using disk diffusion or commercial automated systems in accordance with the standardized China Antimicrobial Surveillance Network (CHINET) surveillance protocol. Results were interpreted using the 2025 Clinical and Laboratory Standards Institute breakpoints. Between January and December 2025, 516,309 clinical isolates were included, comprising 28.5% Gram-positive and 71.5% Gram-negative bacteria. The detection rates of methicillin-resistant strains among Staphylococcus aureus , Staphylococcus epidermidis , and other coagulase-negative staphylococci were 28.4%, 80.8%, and 76.5%, respectively, with no vancomycin-resistant strains identified. Vancomycin resistance among Enterococcus faecium isolates was 8.4%, and resistance to most antimicrobial agents was higher than that among Enterococcus faecalis isolates. Among nonmeningeal Streptococcus pneumoniae isolates from pediatric and adult patients, the respective detection rates of penicillin-nonsusceptible strains, comprising penicillin-intermediate S. pneumoniae and penicillin-resistant S. pneumoniae , were low at 3.9% and 5.9%. Except for Klebsiella spp., which showed resistance rates of 20.1% to imipenem and 20.8% to meropenem, resistance among other Enterobacterales was generally below 15.0%. After excluding intrinsically resistant genera, Enterobacterales remained highly susceptible to tigecycline and colistin, with resistance rates of ≤ 6.8%. Resistance rates to imipenem and meropenem were 22.6% and 18.8%, respectively, in Pseudomonas aeruginosa, and 72.0% and 71.9%, respectively, in Acinetobacter baumannii . Antimicrobial resistance among clinical isolates from major regions of China remained a serious concern in 2025. These surveillance findings should inform rational antimicrobial selection and support efforts to limit the emergence and spread of resistance.